2010
DOI: 10.1097/npt.0b013e3181dde5dd
|View full text |Cite
|
Sign up to set email alerts
|

Does Otolith Organ Dysfunction Influence Outcomes After a Customized Program of Vestibular Rehabilitation?

Abstract: Otolith dysfunction does not significantly influence the response to rehabilitation of individuals with a peripheral vestibular disorder. Vestibular rehabilitation is associated improvements in symptom severity, self-perceived handicap, and balance function in individuals with otolith dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Return to work is an important measure of the benefit of any VPT program; however, few researchers have incorporated a measure of return to work. In 4 level II studies 223,224,248,249 and 4 level III studies, 24,112,129,192 individuals' perceived disability has been reported to positively change after rehabilitation. Although the disability rating scale includes ability to work as a portion of the instrument, no studies specifically report how frequently people with peripheral vestibular hypofunction are able to return to work in the same occupation and capacity after VPT.…”
Section: Quality Of Life: Harm/benefits Ratiomentioning
confidence: 99%
“…Return to work is an important measure of the benefit of any VPT program; however, few researchers have incorporated a measure of return to work. In 4 level II studies 223,224,248,249 and 4 level III studies, 24,112,129,192 individuals' perceived disability has been reported to positively change after rehabilitation. Although the disability rating scale includes ability to work as a portion of the instrument, no studies specifically report how frequently people with peripheral vestibular hypofunction are able to return to work in the same occupation and capacity after VPT.…”
Section: Quality Of Life: Harm/benefits Ratiomentioning
confidence: 99%
“…Improvements in driving have been noted in others with chronic unilateral hypofunction after an exercise program. 105 In 2 level II studies and 3 level III studies, patients' perceived disability has been reported to positively change after rehabilitation. This disability scale includes ability to work as a portion of the instrument, yet no studies specifically report how frequently people are able to return to work effectively after vestibular rehabilitation (level II: Giray et al, 50 Shepard et al, 68 Telian et al 82 ; level III: Shepard et al, 73 Telian et al 60 ).…”
Section: Action Statements and Research Recommendationsmentioning
confidence: 99%
“…This is important because VR is based upon principles of vestibular adaptation of semicircular canal/VOR input. There is some evidence that combined otolith dysfunction and canal dysfunction does not negatively impact rehabilitation outcomes [69]; however, the study did not include individuals with mTBI or otolith-only dysfunction. In contrast, Basta et al [66] have shown that traditional VR is not effective for many patients with otolith disorders.…”
Section: Treatmentmentioning
confidence: 99%